Assessment of immunolocalization of Fas antigen in the ovarian follicle and the role of IGF-I in Fas-L induced granulosa cell apoptosis in water buffalo - Patil, Sunil Kumar; Ravindra, J P; Jamuna, K V; Joseph, Dhanya; Raghvendra, B S; Prasad, R V; Selvaraju, S (The Indian Journal of Animal Sciences, 2012)
Primordial follicle pool size in the ovary is small and rate of follicular atresia is high in water buffaloes. The objective of this experiment was to study the expression of Fas antigen in granulosa cells of water buffalo ovarian follicle, and to know the role of insulin like growth factor-1(IGF-I) on Fas-ligand (Fas-L) mediated apoptosis. The Fas expression was observed mainly in the granulosa cells of the follicles. The expression was higher in the granulosa cells, which were denuded from basement membrane, indicating apoptosis. Healthy follicles which had intact multilaminar granulosa cell layer showed negative reaction for Fas antigen. The granulosa cells from 3–6 mm diameter follicles of the buffalo ovaries collected from the slaughterhouse ovaries were cultured in vitro to assess the effect of Fas-L at 10, 20 and 50ng/ ml on granulosa cell viability. The Fas-L even at the lowest dose tested (10ng/ml) significantly decreased granulosa cells viability as compared to control; whereas addition of IGF-I to the culture significantly improved granulosa cell viability. Addition of IGF-I could significantly improve the granulosa cells viability in the Fas-L treated culture. Overall this study demonstrated the existence of Fas and Fas mediated apoptosis in the granulosa cells of the buffalo follicle, and also suggested that IGF-I could rescue granulosa cells from Fas-L mediated apoptosis.